2004
DOI: 10.1128/aac.48.4.1416-1418.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Haemophilus influenzae tolC Gene by Susceptibility Profiles of Insertionally Inactivated Efflux Pump Mutants

Abstract: Isogenic strains containing insertional disruptions of 10 Haemophilus influenzae Rd genes were investigated for their effects on the susceptibility of the organism to various classes of antimicrobial compounds. MIC results show that HI1462, which encodes an Escherichia coli TolC homolog, is the third component of the H. influenzae AcrAB pump.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…Use of efflux-compromised E. coli strains proved essential for uncovering the mode of action of a new class of bacterial RNA polymerase inhibitor (CBR-703) (1), and this systematic efflux knockout approach has been applied more broadly in studies with Streptococcus pneumoniae (57) and Haemophilus influenzae (64). We know of no other published studies wherein P. aeruginosa efflux-compromised strains have been systematically employed toward the discovery of novel classes of antipseudomonal agents.…”
Section: Discussionmentioning
confidence: 99%
“…Use of efflux-compromised E. coli strains proved essential for uncovering the mode of action of a new class of bacterial RNA polymerase inhibitor (CBR-703) (1), and this systematic efflux knockout approach has been applied more broadly in studies with Streptococcus pneumoniae (57) and Haemophilus influenzae (64). We know of no other published studies wherein P. aeruginosa efflux-compromised strains have been systematically employed toward the discovery of novel classes of antipseudomonal agents.…”
Section: Discussionmentioning
confidence: 99%
“…The substrate specificities of AcrAB EC -TolC EC and AcrAB HITolC HI are very similar and include both positively charged (dyes and erythromycin) and negatively charged (novobiocin) compounds (19,24). In contrast to E. coli, AcrAB HI -TolC HI does not protect H. influenzae from ␤-lactams, chloramphenicol, tetracycline, or fluoroquinolones.…”
mentioning
confidence: 90%
“…In all cases, the susceptibility profiles of AcrA HI , AcrB HI , or TolC HI null mutants were identical, suggesting that these proteins are components of a single pump. Mutations in other RND transporters identified by sequences searches of H. influenzae genome did not affect drug susceptibility (24). Therefore, AcrAB HI -TolC HI is a major, constitutively expressed multidrug efflux complex of H. influenzae and a potent target for the development of specific inhibitors of this transporter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A later study suggested that AcrAB acted together with TolC and showed that the system also pumps out additional compounds such as ampicillin, fusidic acid, linezolid, puromycin, trimethoprim, cholate, Triton X-100, rhodamine 6G, and hexadecyltrimethylammonium bromide (371). A MATE family pump was cloned and produced resistance when expressed in an efflux-deficient E. coli host (16); however, its inactivation in H. influenzae produced little effect on antimicrobial susceptibility (371).…”
Section: Pasteurellaceaementioning
confidence: 99%